The Influence Of Work Stress, Workload, And Work Conflict On Employee Performance At PT. WT Indonesia : PT. WT Indonesia - khoirun neiliya; Ratih Hesty Utami Puspitasari; Ika Indriasari (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The purpose of this study is to analiyze and test the effect of word stress, workload and work conflict on employee performance. This sample is all employees of PT. WT Indonesia who are in the dry production section totaling 105 employees. The sampling technique in this study used saturated sampling (census sample). The data analysis technique used in this study was carried out using the multiple linier regression method with the help of SPSS Version 25 software. Bassed on the results of the study, it shows that work stress has a positive and significant effect on employee performance with a significance value of (0,000), Workload has a negative and significance effect on employee performance with a significance value of (0,000), work conflict has a negative and significance effect on employee performance with a significance value of (0,001).